Arduino Based Light Intensity Auto Curtain - Mursidah; Herry Setiawan; Muhammad Khoiruddin Harahap; Amsar Yunan; Dirja Nur Ilham (ITScience (Information Technology and Science), 2022)
The rapid advancement of technology has led to significant changes in human life. There are numerous tools available, many of which are intended to make human work easier. Science and technology develop, resulting in improved innovations. Automatic control systems have recently advanced at a dizzying pace in the areas of science and technology. This is shown by the variety of applications, which range from residential to sophisticated equipment. GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Meter GY-49 MAX44009 GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Meter GY-49 MAX44009 Lux Ambient light for Arduino is a concept that arose in response to the demands of home automation systems. It is Arduino-based and has light intensity controls. The house's tenants will profit from the renovation. Simply said, the curtains are open while the light intensity is 271 - 1000 lux, closed when the light intensity is 1001 lux and closed when the light intensity is 270 lux so that the light entering the room is not too bright and does not create The room felt hot from too much exposure to the sun. In the age of modernization, this tool is supposed to boost the mobility of the house's occupants.